Secure and Scalable Blockchain Frameworks for Internet of Things (IoT) Networks - Tamara Saad Mohamed (Academic International Journal of Engineering Science, 2023)
The increasing exponentially growing Internet of Things (IoT) networks have posed hitherto unseen challenges, in security, data integrity, and scaling in distributed systems. It provides an ideal technology that solves numerous intrinsic weaknesses of traditional IoT designs such as single point of failure, unauthorized access, and data distortion, which can be resolved by the use of blockchain technology. In this paper, the author will discuss how blockchain frameworks can be implemented in conjunction with IoT networks, the technical structure, consensus algorithms, and security protocols intended to improve the level of reliability and trustworthiness of a system. It is a critical analysis of several blockchain applications such as the public as well as the private model and consortium model and also discusses scalability issues of each model of computational overhead, energy usage, and transaction throughput. The paper discusses novel solutions that include lightweight consensus algorithms, off-chain processing, sharding, and directed acyclic graph designs which are specifically designed to support the resource-constrained IoT devices. This study is shown using case studies in smart cities, healthcare, supply chain management and industrial automation industries to show how blockchain-IoT integration can help minimize security breaches by up to 60 percent without compromising system performance. The paper concludes that scalable and secure blockchain platforms are disruptive platforms to construct trusted, transparent and robust IoT networks in the era of pervasive computing.